Estudo clínico e molecular em pacientes com artrogripose distal - Nicola, Pablo Domingos Rodrigues De [UNIFESP] (2017)
Distal Arthrogryposis (DA) is a group of monogenic diseases of autosomal dominant inheritance, with incomplete penetrance, variable expressivity, characterized by congenital contractions of the distal joints of the limbs, not being caused by defects of the central and peripheral nervous system, by myopathies or by metabolic diseases. Ten different syndromes make up this group, the most common being DA1, DA2A and DA2B. Mutations in genes encoding skeletal muscle proteins (ECEL1, FBN2, MYBPC1, MYH3, MYH8, TNNI2, TNNT3, TPM2 and PIEZO2) are responsible for the etiology of AD. Objective: To describe clinical and molecular findings in patients with AD. To study the genes ACTA1, MYBPC1, MYH3, MYH8, TNNI2, TNNT1, TNNT3 and TPM2, in patients with AD and in their respective parents. To classify patients into syndromic groups and into molecular groups. Method: Evaluation of patients with congenital multiple arthrogryposis according to the clinical protocol. Extraction of genomic DNA from peripheral blood. State-of-the-art sequencing (NGS) using a panel of 8 genes (ACTA1, MYBPC1, MYH3, MYH8, TNNI2, TNNT1, TNNT3, TPM2). Validation of variants found in NGS by performing Sanger sequencing. Results: Among 106 patients with congenital multiple arthrogryposis, 19 subjects fulfilled the inclusion criteria for AD, 14 sporadic cases and 5 familial cases. Among the 19 individuals with AD, 7 individuals presented variants considered pathogenic, being 4 sporadic cases and 3 cases in the same family. Conclusions: Three variants of the MYH3 gene (c.1402T> C, c.2015G> A and c.5254G> T) were reported in individuals with DA1, DA2A and DA2B, two variants never described in the literature; one in the MYH8 gene (c.3349 + 1G> T) in an individual with DA7, not reported in the literature; and one in the TNNT3 gene (c.187C> T) in a sporadic case of DA2B and in 3 familial cases with DA2B that present phenotypic variability.